Energy storage enhancement of paraffin with a solar-absorptive rGO@Ni film in a controllable magnetic field. (1st January 2022) - Yan, Shengnan; Li, Zhenggui; Liu, Xiaobing; Chen, Fang; Li, Wangxu; Cheng, Jie
Graphical abstract: Highlights: A magnetically-tuned method that enhances the surface absorption of solar energy is proposed. rGO@Ni foam was employed to improve the photothermal conversion of paraffin. The paraffin phase interface was dynamically regulated using a controllable magnetic field. The efficiency of thermal energy storage improved by about 29%. Phase interface motion improved by about 50%. Abstract: Magnetically driven photothermal conversion and energy storage techniques can enhance the energy storage performance of phase change materials (PCMs) and thus have immense potential in energy applications. Paraffin is a common PCM that melts slowly and has poor rate of heat storage capacity. In this study, the effect of a controllable magnetic field on the photothermal and heat storage properties of paraffin was investigated. First, a reduced-graphene-oxide/nickel foam (rGO@Ni foam) composite film with good photothermal ability, corrosion resistance, and oxidation resistance was prepared, and photothermal conversion and energy storage processes under different magnetic fields were experimentally studied. The movement of the composite film could be adjusted by the action of magnetic force, especially to enhance the phase interface movement, accelerate paraffin melting, and improve the photothermal capacity and heat storage characteristics of the material. The composite film and phase interface could be dynamically tuned by regulating the magnetic field, thus enhancing the photothermal conversion effect. In particular, with increasing magnetic field strength, the thermal energy storage efficiency and speed of phase interface movement increased by 29% and 50%, respectively. The proposed magnetic force-driven method will enhance solar energy conversion and promote direct solar energy applications.